Towards the determination of metal criticality in home-based battery systems using a Life Cycle Assessment approach. (1st June 2019) - Terlouw, Tom; Zhang, Xiaojin; Bauer, Christian; Alskaif, Tarek
Abstract: The operation and production of batteries is associated with environmental impacts that can be quantified with Life Cycle Assessment methodologies. Current life cycle impact assessment methodologies do not assess metal criticality: they are based on geological availability or resource depletion only and do not consider socio-economic factors. Such factors are included by the concept of metal criticality. This paper determines the metal criticality of six home-based battery systems (Li-Ion: LFP-C, NMC-C, NCA-C, NCA-LTO; VRLA battery and the VRFB) for a photovoltaics self-consumption application based on a Life Cycle Assessment approach. Cumulative life cycle inventory results on extraction of metal resources are coupled with characterization factors of 13 metals derived from three state-of-the-art criticality methodologies. The results are presented for two functional units: (1) the installed battery system per kWh of energy delivered (per cycle); (2) additionally including necessary replacements of battery packs during the system lifetime. Due to substantial differences in terms of battery lifetimes between battery technologies, the latter functional unit turns out to be more meaningful. In general, there is a correlation between lower metal criticality scores (i.e. better performance) and batteries with a higher specific energy, longer battery lifetime and lower mass of metal consumption. LFP-C battery shows both low metal criticality scores and comparatively robust results, while VRFB exhibits low metal criticality but associated with relatively high uncertainties. In contrast, the VRLA battery performs the worst due to low discharge efficiency and relatively short battery lifetime. We argue that metal criticality could be reduced by improving the specific energy of the battery, by selecting low metal-intensive and low-critical metal containing components, by increasing the use of secondary metals and by selecting batteries with longer battery lifetimes. Highlights: Battery lifetime is a key factor for metal criticality assessment of batteries. Valve Regulated Lead Acid battery performs worst in terms of metal criticality. Abundant metals used in high quantities (Al, Cu, Fe) contribute most to criticality. Cobalt, despite minor quantitative use, contributes substantially to criticality. Metal criticality reduces by recycling, high energy density and longer lifetime.